PENGUATAN PENDIDIKAN KARAKTER DISIPLIN PADA PESERTA DIDIK MELALUI PEMBERIAN REWARD DAN PUNISHMENT DI SD UNGGULAN USWATUN HASANAH - Sari, Dewi Aprilia; Jamaludin, Ujang; Taufik, M. (ATTA`DIB, 2019)
The current character education is important to implement and be taught at the base. Especially in order to right-hand the students ' disciplinary character. Reward and punishment are one of the ways that can be used to implement the strengthening of discipline character education. This research aims to determine how the implementation of education strengthening the character disciplines through the awarding of reward and punishment in the SD Unggulan Uswatun Hasanah. The method used in this research is a qualitative method, with a qualitatively descriptive type. The data collection techniques used in this research are observation and interview techniques, which are then conducted analysis with the Miles and Huberman models. The results of this study can reveal that the students in SD Uswatun Hasanah are as follows: (1) The implementation of reward and punishment in strengthening the character education discipline in the students at SD Unggulan Uswatun Hasanah. a Implementation planning conducted by the 3rd class Ummar Hayyam in the learning by creating a learning implementation plan that lists the rewards and punishment, as well as in the activities of the class by arranging a picket schedule, orderly dispose of Strengthening the discipline of character education in learners. b. Implementation planning conducted by the principal by arranging school activities that include the extracurricular scout and extracurricular, Tahfidz, discipline activities with Jumsih program and the cleanest race, and Apply rewards and punishment. c. The implementation process using techniques, methods, and stages in the implementation of the strengthening of discipline character education (2) The role of educational reinforcement character discipline in students through the giving of reward and punishment that is seen from his behavior and responsibilities as a student in the primary SD Uswatun Hasanah. (3) The results of strengthening the education of the character is disipin through reward and punishment to the students at SD flagship Uswatun Hasanah is emphasizing the discipline of learners, foster a passion for learners, and also Foster an honest attitude towards learners.